Adapted statistical experiments - Koroliouk, D.V. (Український математичний вісник, 2016)
We study statistical experiments with random change of time, which transforms a discrete stochastic basis in a continuous one. The adapted stochastic experiments are studied in continuous stochastic basis in the series scheme. The transition to limit by the series parameter generates an approximation of adapted statistical experiments by a diffusion process with evolution.